Analysis of Public Facilities, Village Funds and Social Infrastructure on Community Welfare in Pematang Serai Village, Langkat Regency - Rahmad Sembiring; Annisa Ilmi Faried; Uswatun Hasanah; Ramses Ginting (International Journal of Management, Economic and Accounting, 2024)
This research is based on the analysis of public facilities, village funds and social infrastructure on the welfare of the community in Pematang Serai village. Pematang Serai village, Langkat Regency is dominated by people who earn a living as fruit and vegetable farmers, but with the location of the village far from the city, there is a need for attention to public facilities for the community, Good management of village funds and infrastructure to be a benchmark for community welfare and household productivity is important for the people who live in the village. This research was conducted in Pematang Serai Village. The thing being studied is the influence between the variables of public facilities, village funds, and social infrastructure, on community welfare and household productivity. The purpose of the research is to find out and analyze the welfare of the community in Cingkes Village, Dolok Silau District by analyzing through public facilities, management and villages for the community and social infrastructure to facilitate daily community activities. The number of samples used was 200 data families collected by distributing questionnaires and data management using SEM (Structural Equation Modeling) using Amos software version 20. Based on the results of the test conducted with a hypothesis test, social infrastructure variables have a significant effect on community productivity. Then the variables of public facilities, village funds and social infrastructure have an insignificant effect on the welfare of the community and the variables of facilities and village funds also have no significant effect on household productivity. In this study, it is hoped that the village government will pay more attention to the things that the community needs in the village.